Perlindungan Logo Merek Organisasi Yang Didaftarkan Atas Nama Pribadi (Studi Kasus Putusan No. 3/Pid.Sus/2017/PN Btl. (Hak Cipta) - Permana, Yana Sukma; Santoso, Soegiharto; Kemala, Ratih (PT Elaborium Elevasi Indonesia, 2024)
Intellectual Property Rights (hereinafter abbreviated to HKI) have a very important position in the current modern era where HKI has become a benchmark in national economic development. Developed countries rely on their country's economic strength from intellectual property as the driving force of their economy. HKI are exclusive rights granted to a person or group of people for their creative works. In simple terms, HKI includes Copyright, Patent Rights and Trademark Rights. This writing is the result of research using normative legal research methods with descriptive research specifications and the experience of Soegiharto Santoso who has been involved as a Management since 1995 and served as General Chair of APKOMINDO for 2 (two) periods 2015-2019 and 2019-2023. In this method, the main data are primary legal materials in the form of legislation related to the implementation of elections and campaigns in Indonesia, secondary legal materials in the form of related books, and tertiary legal materials in the form of legal research journals and other scientific articles. This secondary data was collected through library study techniques and grouped according to the type of legal material, including additional information obtained from Soegiharto Santoso. That Sonny Franslay on December 13 1991 was the initiator of the formation of APKOMINDO (Indonesian Computer Entrepreneurs Association), which initially only had a scale in Jakarta and was non-profit. All association income obtained from member fees will be used entirely to finance the association's activities. Some names that are worth noting as founding fathers of APKOMINDO are Sonny Franslay, Ir. Chris Irwan Japari, Ir. Wiriadi Tirtariyadi, Efendi Ruslim, John Franco, Agus Setiawan and the late. Daniel Tjahyadi. Furthermore, in 2000 in Yogyakarta, entrepreneurs from various regions in Indonesia gathered, including previously recorded as having established APKOM JATIM and APKOM YOGYA, where all organizations agreed to unite into APKOMINDO and become a national-scale, non-profit organization. Then on April 14 2016 Soegiharto Santoso was reported to the Police Criminal Investigation Unit regarding the violation of the APKOMINDO logo copyright, until he was detained for 43 days and tried and was found not guilty at both the first level and the cassation level.